Analysis of Chemistry Education Students' Perceptions Regarding the Use of ChatGPT for Organic Chemistry Learning - Fikriya, Sakti Hidayati; Zulqurnain, Muhammad; Suharman, Andi; Ad’hiya, Eka (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Advances in artificial intelligence technologies, such as ChatGPT, provide new opportunities for learning Organic Chemistry, a subject noted for its abstract and complex concepts. The purpose of this study is to investigate students' impressions of using ChatGPT as a learning tool for mastering Organic Chemistry subjects. This descriptive quantitative study included 87 Chemistry Education Study Program students from Sriwijaya University's Faculty of Teacher Training and Education. A Likert-scale survey was used to obtain data on frequency of usage, perception of use, perception of utility, prompt effort, and ethical awareness when using ChatGPT. The results revealed that 98.9% had used ChatGPT to learn Organic Chemistry; 74% thought ChatGPT was successful in promoting understanding of the content; and 72% recognized the efficiency of learning time. Thematic study revealed that ChatGPT aided in the smooth exposition of difficult concepts such as stereochemistry and chemical processes. However, 59% believed that the explanations' accuracy required further scientific validation. Respondents acknowledged the possibility of conceptualization errors if ChatGPT was utilized without lecturer guidance or evaluation of scientific sources. These findings support ChatGPT's potential as an adaptable and relevant Organic Chemistry learning tool for achieving 21st-century demands such as critical thinking and problem solving. Additional study recommendations include integrating ChatGPT into organic chemistry learning models and media.